Research on the Artistic Characteristics of Chinese Ballet in the 21st Century - Chen, Jingya; Rattanachaiwong , Nataporn; Jin , Qianqiu (Journal of Dhamma for Life, 2025)
This study examines the evolving artistic characteristics of Chinese ballet in the 21st century through a multidimensional lens. It explores the integration of traditional Chinese culture with global artistic trends and highlights the innovative transformations in performance and choreography. Specifically, the research focuses on two core objectives: (1) to investigate how Chinese ballet has embraced cultural integration and creative expression within the context of globalization, and (2) to analyze the emerging trends shaped by modern science and technology, as well as the development of individualized artistic styles. Employing a combination of literature review, observational analysis, and qualitative interviews, this study systematically identifies the characteristics of stage presentation, narrative techniques, and artistic expression in contemporary Chinese ballet theatre. The findings indicate that Chinese ballet has cultivated a distinctive artistic identity by blending Eastern and Western elements, achieving notable innovation in both form and content. This progression not only reinforces the cultural identity of Chinese ballet but also enhances its visibility and impact on the global stage, offering valuable theoretical insights for its continued development and international recognition.